1999
DOI: 10.1016/s1044-0305(98)00116-0
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-assisted laser desorption/ionization mass spectra reflect solution-phase zinc finger peptide complexation

Abstract: The complexation between an 18-residue zinc finger peptide of CCHC type (CCHC = Cys-X2-Cys-X4-His-X4-Cys, X = variable amino acid) from the gag protein p55 of human immunodeficiency virus type 1 (HIV-1) and various transition metal ions was studied by means of circular dichroism spectroscopy and matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). A correlation between the complexation behavior in solution and in MALDI-MS could be established. It was shown that MALDI-MS is a fast method su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…[9] A preliminary MALDI-MS study of the complexation between p55F1 and various metal ions was performed in our laboratory. [10] We found that the Zn ± p55F1 complex detected is specific, and that the complex formation observed qualitatively correlates with that in solution (see also reference [11]). …”
supporting
confidence: 52%
See 1 more Smart Citation
“…[9] A preliminary MALDI-MS study of the complexation between p55F1 and various metal ions was performed in our laboratory. [10] We found that the Zn ± p55F1 complex detected is specific, and that the complex formation observed qualitatively correlates with that in solution (see also reference [11]). …”
supporting
confidence: 52%
“…The reasons in the case of Zn ± p55F1 have already been discussed. [10] Similar arguments can also be made for the triple complex: Variations in desorption, ionization, and detection efficiencies among the triple complex, the Zn ± p55F1 complex, the peptide (present in excess), and d(TTGTT) as well as partial peptide oxidation or partial dissociation of the complex ions upon crystallization or during the MALDI process may all contribute to the triple complex signal being less intense than that of the components. From this, it is clear that absolute abundances of the species in solution (the complex and its components) and peak intensities in the MALDI mass spectra cannot be directly compared.…”
mentioning
confidence: 79%
“…The fact that only in cases when the peptide contains an acidic functional group are these ions observed provides evidence for their formation from a cluster such as fnT-M-B -Zn 2C g C and evaporation of HB. It therefore appears questionable whether MALDI results reported on peptide-Zn complexation truly represent specific Zn 2C adduction, 67 unless a true dominance of the complex signal at stochiometric Metal nC addition is detected. 68 It is important to note that the intermediate formation of 'anionized' clusters and the subsequent evaporation of neutral acids after proton transfer form a general pathway for the formation of deprotonated negative ions without the need to consider acid-base charge disproportionation.…”
Section: Formation Of Final Gas-phase Ions and The Essential Action Omentioning
confidence: 99%
“…For this reason, the FT-ICR MS technique has been combined with the soft ionization technique MALDI using internal [23][24][25][26][27][28] as well as external [29 -37] ion sources. One of the striking advantages of the MALDI FT-ICR technique is high sensitivity as well as high throughput capability.Many ion chemistry studies show similarities between the behavior of gas-phase ions and equivalent species in the condensed phase [38,39]. As the amount of structural information emerging from gas-phase ion studies increases, MS techniques, particularly in combination with H/D exchange reactions, are playing an increasingly important role in structural analysis of biomolecules [40 -47].…”
mentioning
confidence: 99%
“…Many ion chemistry studies show similarities between the behavior of gas-phase ions and equivalent species in the condensed phase [38,39]. As the amount of structural information emerging from gas-phase ion studies increases, MS techniques, particularly in combination with H/D exchange reactions, are playing an increasingly important role in structural analysis of biomolecules [40 -47].…”
mentioning
confidence: 99%